SUPERVISION OF THE DISTRIBUTION OF 3 KG SUBSIDIZED LPG GAS FROM THE PERSPECTIVE OF MAQASHID SYARIAH: (A Case Study at a Distribution Base in Kuala Batee Subdistrict, Southwest Aceh Regency) - Fachrol juanda; Mustaqilla, Safira; Fauzan, Faisal (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
Abstract The distribution of subsidized LPG is part of the government’s policy to ensure access to basic energy needs for low-income communities. However, in practice, several irregularities persist, including off-target distribution, prices exceeding the official Retail Price Ceiling (HET), and weak oversight mechanisms at the base distribution level. This study aims to examine the supervision system in the distribution of 3-kg subsidized LPG cylinders in Kuala Batee District, Southwest Aceh Regency, and to assess the extent to which current distribution practices align with the principles of Maqashid Syariah. This research employs a qualitative method with a descriptive-analytical approach. Data were collected through field observation, in-depth interviews with LPG outlet owners, five subsidy recipients from the local community, one relevant village official, and a review of policy and regulatory documents. The findings were analyzed within the framework of Maqashid Syariah, focusing on the principles of hifz al-mal (protection of wealth) and hifz al-nafs (protection of life). The results indicate that the existing supervision of LPG distribution remains ineffective. Key issues include the misidentification of eligible recipients, inconsistent pricing beyond regulatory limits, and the absence of a robust verification system. From the perspective of Maqashid Syariah, such shortcomings not only undermine social justice but also hinder the realization of public welfare. Therefore, improvements are needed in the form of data-driven distribution systems, collaborative oversight, and public education to ensure that LPG subsidies are distributed fairly and in accordance with Islamic ethical values.